Anti-corrosion polyurethane composite protective film for battery and preparation method of anti-corrosion polyurethane composite protective film

By using a composite material of fluorosilicone resin and polyurethane emulsion and a methylated guar-based composite material, the battery protection film is prepared, and the problem of poor heat resistance of the protective film in the prior art in high temperature environment is solved, and higher thermal stability and insulation performance are achieved.

CN119615635AActive Publication Date: 2025-03-14GUANGZHOU FUSIDA CHEM PROD CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510153503.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-12
Publication Date
2025-03-14
Estimated Expiration
2045-02-12

AI Technical Summary

Technical Problem

The existing battery protective film has poor heat resistance in high-temperature environments, resulting in softening and melting, affecting performance and life. At the same time, there are also problems with its surface hydrophobicity and water vapor barrier properties.

Method used

A composite material of fluorosilicone resin and polyurethane emulsion is used to prepare a fluorosilicone/polyurethane film through electrospinning technology, and the surface is coated with methylated guar-based composite material as an outer layer film to improve heat resistance and insulation performance.

Benefits of technology

It significantly improves the thermal stability, corrosion resistance and insulation properties of the battery protective film, extends the battery life and reduces the risk of thermal runaway.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides an anti-corrosion polyurethane composite protective film for a battery and a preparation method of the anti-corrosion polyurethane composite protective film, and belongs to the technical field of battery protective materials, and the preparation method comprises the following steps: mechanically stirring and uniformly mixing fluorosilicone resin, polyurethane emulsion, propylene glycol methyl acetate and triphenyl phosphite, and performing ultrasonic treatment and heating dehydration to prepare fluorosilicone / polyurethane emulsion; the preparation method comprises the following steps: mixing methylated guar gum powder, a hydrophobic nano-clay aqueous suspension and an ethanol dispersion liquid of nano aluminum oxide and nano titanium dioxide, and then carrying out ultrasonic treatment and mechanical stirring to prepare a methylated guar gum-based composite material; the preparation method comprises the following steps: preparing a fluorosilicone / polyurethane film from a fluorosilicone / polyurethane emulsion through electrostatic spinning, adding polytetrahydrofuran diamine into a methylated guar gum-based composite material, stirring, coating on the fluorosilicone / polyurethane film, and standing and curing to obtain the anti-corrosion polyurethane composite protective film. According to the invention, the thermal stability and insulativity can be improved while the battery is protected from being corroded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of battery protection materials, and in particular to an anti-corrosion polyurethane composite protective film for a battery and a preparation method thereof. Background Art

[0002] Common battery casings are generally made of metal (such as steel, aluminum) materials, which will corrode the casing under the action of ultraviolet rays, oxygen and moisture, reducing the battery life. Therefore, a battery casing protective film is needed to protect it from water vapor and other substances in the air.

[0003] During the operation of the battery, heat is generated inside the battery. However, in the current existing technology, the protective film for the battery often shrinks after a period of use. This is because its thermal stability does not meet the standard. In a high temperature environment, the protective film softens and melts due to poor heat resistance, affecting its performance and life, causing the protective film to fail, increasing the risk of thermal runaway of the battery, and there are also certain problems with its surface hydrophobicity and water vapor barrier properties.

[0004] Waterborne polyurethane is an environmentally friendly and inexpensive block copolymer that has attracted great attention in recent years. Its structure contains a two-phase domain, a rigid segment and a soft segment. The rigid segment ensures the spatial stability of waterborne polyurethane, while the soft segment provides good ionic conductivity after dissolving alkali metal salts. Based on the special microstructure, waterborne polyurethane has good mechanical strength, excellent thermal stability and easy film-forming ability, but the battery releases some corrosive gases such as hydrogen and acidic vapor during charging and discharging. The chemical resistance of waterborne polyurethane is generally poor, and it may be corroded by these substances, resulting in degradation or rupture of the film layer. In addition, in order to prevent battery short circuits, improve battery cycle life and safety issues, the protective film needs to have certain insulation functions. In summary, the protective film for batteries needs to have good thermal stability, corrosion resistance and insulation, and these requirements are often difficult to meet for protective films made of a single material.

[0005] Therefore, it is necessary to provide an anti-corrosion polyurethane composite protective film for batteries and a preparation method thereof to solve the problems existing in the above-mentioned prior art. Summary of the invention

[0006] In view of this, the present invention provides an anti-corrosion polyurethane composite protective film and a preparation method thereof, which can protect the battery from corrosion while improving thermal stability and insulation.

[0007] To achieve the above object, the present invention provides a method for preparing an anti-corrosion polyurethane composite protective film for a battery, comprising the following steps: Step S1, mixing fluorosilicone resin, polyurethane emulsion, propylene glycol methyl acetate, and triphenyl phosphite by mechanical stirring, ultrasonic treatment, heating and dehydration, to obtain fluorosilicone / polyurethane emulsion; Step S2, mixing methylated guar gum powder, hydrophobic nano-clay water suspension, nano-alumina alcohol dispersion, and nano-titanium dioxide, ultrasonically treating, and mechanically stirring to obtain a methylated guar gum-based composite material; Step S3, after preparing a fluorosilicone / polyurethane film by electrostatic spinning of a fluorosilicone / polyurethane emulsion, adding polytetrahydrofuran diamine to the methylated guar gum-based composite material, stirring, coating the fluorosilicone / polyurethane film, and standing to cure to obtain an anti-corrosion polyurethane composite protective film.

[0008] The present invention prepares a fluorosilicone / polyurethane emulsion by mixing a fluorosilicone resin and a polyurethane emulsion; the high-bond-energy Si-O bond in the fluorosilicone resin can give it excellent thermal stability, the fluorocarbon chain can effectively reduce the surface tension of the material, and the high bond energy of the CF bond makes it difficult to break at high temperature, the electron negativity of the fluorine atom is strong, so that the CF bond has extremely high hydrophobicity and electrical insulation performance, and the fluorine-containing polymer is highly inert in many chemical environments, and then the fluorosilicone resin is added to the polyurethane emulsion to effectively improve its overall insulation, thermal stability and corrosion resistance; however, due to the difference in solubility parameter values, the compatibility of the fluorosilicone resin and the polyurethane emulsion is not good, and phase separation occurs during blending to form an unstable mixture. In the process of preparing the fluorosilicone / -polyurethane emulsion, propylene glycol methyl acetate is added as a solvent to improve the dispersibility of the fluorosilicone resin in the whole system and improve the compatibility between the fluorosilicone resin and the polyurethane emulsion, and triphenyl phosphite is used as a thermal stabilizer to improve the stability of the polymer under high temperature conditions and prevent its thermal degradation.

[0009] The present invention prepares a methylated guar gum-based composite material as an outer layer membrane, and uses a bio-based material methylated guar gum mixed with nano clay as a base material. Since the hydrophilic guar gum and the hydrophobic nano clay have poor compatibility and uneven dispersion, the methylated guar gum is used. The presence of the hydrophobic methyl group increases the interaction between the hydrophobic group and the hydrophobic nano clay, thereby improving the tensile strength and elongation at break of the prepared nano composite material, and also makes the overall structure more compact and improves the barrier to water vapor, oxygen, etc.; in addition, the nano clay itself is an insulating material with a lower electrical conductivity, further improving the overall insulation performance. Nano alumina and nano titanium dioxide are added to the composite base material as fillers, wherein the nano alumina has a stable surface, has corrosion resistance and is not easily corroded by chemical substances, and titanium dioxide has good antibacterial, anti-oxidation, and UV resistance effects, can reduce the yellowing coefficient of the protective film, and further improve the anti-corrosion and anti-oxidation effects.

[0010] The anti-corrosion polyurethane composite protective film prepared by the present invention adopts a double-layer film composite structure. The inner film is prepared by using the prepared fluorosilicone / polyurethane emulsion through electrostatic spinning technology to prepare a fluorosilicone / polyurethane protective film with good insulation, thermal stability and certain corrosion resistance. The anti-corrosion film is prepared by electrostatic spinning instead of the high-temperature hot pressing preparation process, which avoids the risk of fracture in the film at high temperature and causing water molecules to invade the battery surface. Polytetramethyleneimine is used as a curing agent and mixed with a methylated guar gum-based composite material and then coated on the surface of the inner film as an outer film, thereby improving water resistance and further improving the overall corrosion resistance.

[0011] Optionally, in step S1, polyester resin is added before mechanical stirring, the speed of mechanical stirring is 25 rpm, the time is 1-2 h, the time of ultrasonic treatment is 10-20 min, the temperature of heating dehydration is 160° C.-200° C., and the time is 3-5 h.

[0012] Optionally, the methylated guar gum powder in step S2 is prepared by mixing and stirring a 1% guar gum aqueous solution, sodium hydroxide and methyl iodide under a nitrogen inert atmosphere for 2.5 to 3 hours, adding acetic acid to adjust the pH value of the solution to 7.0, adding acetone, filtering and retaining the precipitate, adding 50% acetone solution to wash three times, and then freeze-drying.

[0013] The present invention uses iodomethane to modify guar gum. During the methylation process, the methyl group (-CH 3 ) groups replace part of the hydroxyl groups in the guar gum molecules through substitution reactions, introducing hydrophobic methyl groups while reducing -OH groups, which also reduces the sites that can form hydrogen bonds, thereby reducing the material's affinity for water and reducing the disorder caused by hydrogen bonds, making the molecules more tightly arranged, thereby enhancing the overall thermal stability. A small amount of unmethylated guar gum has a certain adhesion that can improve the adhesion between the layers of the composite material.

[0014] Optionally, in step S2, hyperbranched graphene oxide is also added before mixing and stirring.

[0015] The invention adds hyperbranched graphene oxide as a filler into a methylated guar gum-based composite base material, wherein, compared with common graphene, graphene oxide with a high oxidation degree generally exhibits good electrical insulation, and the oxygen-containing functional groups of graphene oxide destroy the original π-electron conjugated system of graphene, so that the electrical conductivity is significantly reduced, thereby giving the material good insulation performance, and hyperbranching treatment improves graphene oxide so that the graphene oxide sheets are more closely combined with nano-alumina, nano-titanium dioxide and a matrix, thereby increasing the interface force, and further improving the water resistance and insulation of the methylated guar gum-based composite material.

[0016] Optionally, the hyperbranched graphene oxide is prepared by stirring a graphene oxide sheet suspension and γ-glycidyloxypropyltrimethoxysilane, adding an acetic acid solution with a concentration of 66.7%, reacting at 75°C for 24 hours, and drying at 24°C for 40 hours; the graphene oxide sheet suspension is prepared by dispersing graphene oxide sheets in an anhydrous ethanol solution and ultrasonically treating them for 20 minutes.

[0017] In order to make the graphene oxide sheet better combined with the body, the present invention uses γ-glycidyloxypropyltrimethoxysilane (KH-560) as a hyperbranched polysiloxane, which contains multiple functional groups in its molecular structure, so that a highly branched network can be formed during the polymerization process. The hyperbranched polysiloxane is grafted onto the graphene oxide sheet through acid hydrolysis to form hyperbranched graphene oxide.

[0018] Optionally, in step S2, the ultrasonic treatment time is 1 to 2 hours, the mechanical stirring speed is 20 rpm, and the time is 30 to 60 minutes; the concentration of the hydrophobic nanoclay water suspension in step S2 is 5% to 10%, and the model of the nanoclay in the hydrophobic nanoclay water suspension is Cloisite 20A.

[0019] In the present invention, the concentration of the hydrophobic nanoclay water suspension is 5% to 10%, and the best effect is achieved. A too high concentration of the hydrophobic nanoclay water suspension will reduce the overall tensile strength. The use of hydrophobic clay improves the overall hydrophobicity and reduces the water vapor permeability.

[0020] Optionally, in step S3, the electrospinning time is 2 hours, the fluorosilicone / polyurethane film after electrospinning is placed under natural conditions to dry for 12 to 24 hours, the stirring time is 15 to 20 minutes, and the static curing temperature is 20 to 30°C and the time is 32 to 48 hours.

[0021] Optionally, the anti-corrosion polyurethane composite protective film for batteries comprises the following raw materials in parts by weight: 3 to 5 parts of fluorosilicone / polyurethane emulsion, 0.2 to 0.8 parts of polytetramethylenediamine, and 3 to 7 parts of methylated guar gum-based composite material.

[0022] Optionally, the raw materials of the fluorosilicone / polyurethane emulsion include 20-50 parts of fluorosilicone resin, 40-60 parts of polyurethane emulsion, 40 parts of propylene glycol methyl acetate, and 5 parts of triphenyl phosphite, calculated by weight; the raw materials of the methylated guar gum-based composite material include 10-20 parts of methylated guar gum powder, 65-80 parts of hydrophobic nanoclay water suspension, and 10-15 parts of ethanol dispersion of nano-alumina and nano-titanium dioxide, calculated by weight.

[0023] Optionally, the raw materials of the methylated guar gum powder include 250 parts of guar gum aqueous solution, 6.25 parts of sodium hydroxide, and 2 parts of methyl iodide, calculated by weight.

[0024] The above technical solution of the present invention includes at least the following beneficial effects: The present invention adds fluorosilicone resin to a polyurethane suspension to improve its overall insulation, thermal stability and corrosion resistance, uses propylene glycol methyl acetate as a solvent to improve the dispersibility of the fluorosilicone resin in the entire system, and improves the compatibility between the fluorosilicone resin and the polyurethane emulsion, and uses triphenyl phosphite as a thermal stabilizer to improve the stability of the polymer under high temperature conditions and prevent thermal degradation thereof.

[0025] The present invention prepares a methylated guar gum-based composite material as an outer layer membrane, wherein the interaction between the hydrophobic methyl group in the methylated guar gum and the hydrophobic group in the hydrophobic nano-clay is increased, so that the overall structure is more compact, and the tensile strength and elongation at break of the prepared nano-composite material and the barrier property to water vapor, oxygen, etc. are further improved. Nano-alumina and nano-titanium dioxide are used as fillers to further improve the anti-corrosion and anti-oxidation effects.

[0026] The anti-corrosion polyurethane composite protective film prepared by the present invention adopts a double-layer film composite structure, the inner film is a fluorosilicone / polyurethane protective film, and is prepared by electrostatic spinning instead of a high-temperature hot pressing preparation process, thereby avoiding the risk of fractures in the film at high temperatures causing water molecules to invade the battery surface. The methylated guar gum-based composite material prepared by coating with polytetramethyleneimine as a curing agent is used as an outer film, thereby improving water resistance and further enhancing the overall corrosion resistance. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described in combination with the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, not all the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.

[0028] Preparation: Add 1 part of nano-alumina and 1 part of nano-silicon dioxide into 10 parts of anhydrous ethanol solution and ultrasonically treat for 20 minutes to prepare an ethanol dispersion of nano-alumina and nano-titanium dioxide.

[0029] Example 1 25 parts of fluorosilicone resin, 60 parts of polyurethane suspension, 40 parts of propylene glycol methyl acetate and 5 parts of triphenyl phosphite were mixed at a speed of 25 rpm for 1.5 hours, ultrasonic treatment was introduced at a frequency of 20 kHz and a power of 1.5 kW for 10 minutes, and then heated to 180°C and dehydrated for 4 hours to obtain a fluorosilicone / polyurethane emulsion.

[0030] 1 part of graphene oxide sheet was added to 10 parts of anhydrous ethanol solution, and ultrasonic treatment was performed for 20 minutes to obtain a graphene oxide sheet suspension; 8 parts of graphene oxide sheet suspension and 5 parts of γ-glycidyloxypropyltrimethoxysilane (KH-560) were stirred for 15 minutes to mix, and 66.7% acetic acid solution was slowly added to the solution, and the pH value was adjusted to about 5. After reacting at 75°C for 24 hours, it was dried at 24°C for 40 hours to obtain hyperbranched graphene oxide; 250 parts of 1% guar gum aqueous solution, 6. 25 parts of sodium hydroxide and 2 parts of iodomethane were mixed and stirred for 2.5 hours under a nitrogen inert atmosphere, and then acetic acid was added to adjust the pH value of the solution to 7.0. After adding 250 parts of acetone to precipitate the synthetic product, the precipitate was washed 3 times with 200 parts of 50% acetone solution to remove any unreacted chemicals and salts formed during the neutralization process, and freeze-dried to obtain methylated guar gum powder; 15 parts of methylated guar gum powder were dissolved in 45 parts of 7% hydrophobic nanoclay water suspension (nanoclay model: Cloisite 20A), 8 parts of ethanol dispersion of nano-alumina and nano-titanium dioxide and 0.2 parts of hyperbranched graphene oxide were added, and after ultrasonic treatment for 1 hour, mechanical stirring was carried out at 20 rpm at room temperature for 30 minutes to obtain a methylated guar gum-based composite material.

[0031] 3.5 parts of fluorosilicone / polyurethane emulsion were injected into a 10ml syringe and installed on the syringe pump. The catheter was connected through the female Luer head, and then the spinning nozzle was connected through the male Luer head. At the same time, the spinning nozzle was clamped on the high-voltage power supply and adjusted to a suitable position. Subsequently, the spinning substrate aluminum foil was wrapped on the roller receiving the spinning device. The spinning parameters were set as follows: solution push speed 2.0ml / h, spinning nozzle moving speed 2.3mm / s, substrate spacing 14cm, roller-type aluminum foil receiving substrate, rotation speed 235r / min, spinning DC voltage 12.1kV, stable spinning for 2h; the film after electrospinning was placed under natural conditions for drying for 24h to allow the solvent in the film to completely evaporate, and a fluorosilicone / polyurethane film was obtained.

[0032] 0.4 parts of polytetrahydrofuran diamine were added to 4 parts of methylated guar gum-based composite materials, and then gently stirred at room temperature for 20 minutes, and brushed with a brush at 180 g / m 2After being coated on the fluorosilicone / polyurethane film at a coating rate of , it was allowed to stand at 30°C for 48 hours to cure, thereby obtaining an anti-corrosion polyurethane composite protective film.

[0033] Example 2 50 parts of fluorosilicone resin, 60 parts of polyurethane suspension, 40 parts of propylene glycol methyl acetate and 5 parts of triphenyl phosphite were mixed uniformly with mechanical stirring at a speed of 25 rpm for 2 hours, ultrasonic treatment was introduced at a frequency of 20 kHz and a power of 1.5 kW for 20 minutes, and then heated to 200°C and dehydrated for 5 hours to obtain a fluorosilicone / polyurethane emulsion.

[0034] 250 parts of 1% guar gum aqueous solution, 6.25 parts of sodium hydroxide and 2 parts of iodomethane were mixed and stirred for 3 hours under a nitrogen inert atmosphere, and then acetic acid was added to adjust the pH value of the solution to 7.0. After adding 250 parts of acetone to precipitate the synthetic product, the precipitate was washed 3 times with 200 parts of 50% acetone solution to remove any unreacted chemicals and salts formed during the neutralization process, and freeze-dried to obtain methylated guar gum powder; 20 parts of methylated guar gum powder were dissolved in 80 parts of 20% hydrophobic nanoclay aqueous suspension (nanoclay model: Cloisite 20A), 10 parts of ethanol dispersion of nano-alumina and nano-titanium dioxide were added, and after ultrasonic treatment for 2 hours, mechanical stirring was carried out at 20 rpm at room temperature for 60 minutes to obtain a methylated guar gum-based composite material.

[0035] Inject 5 parts of fluorosilicone / polyurethane emulsion into a 10ml syringe and install it on the syringe pump, connect the catheter through the female Luer head, and then connect the spinning nozzle through the male Luer head. At the same time, clamp the spinning nozzle on the high-voltage power supply and adjust the nozzle to a suitable position. Then, wrap the spinning substrate aluminum foil on the roller receiving the spinning device. Set the spinning parameters as follows: solution push speed 2.0ml / h, spinning nozzle moving speed 2.3mm / s, substrate spacing 14cm, roller-type aluminum foil receiving substrate, rotation speed 235r / min, spinning DC voltage 12.1kV, stable spinning for 2h; place the electrospun film under natural conditions to dry for 24h, so that the solvent in the film can be completely volatilized, and obtain a fluorosilicone / polyurethane film.

[0036] 0.5 parts of polytetrahydrofuran diamine were added to 5 parts of methylated guar gum-based composite materials, and then gently stirred at room temperature for 20 minutes, and then brushed with a brush at 180 g / m 2 After being coated on the fluorosilicone / polyurethane film at a coating rate of , it was allowed to stand at 30°C for 48 hours to cure, thereby obtaining an anti-corrosion polyurethane composite protective film.

[0037] Example 3 40 parts of fluorosilicone resin, 20 parts of polyester resin, 30 parts of polyurethane suspension, 40 parts of propylene glycol methyl acetate and 5 parts of triphenyl phosphite were mixed by mechanical stirring at a speed of 25 rpm for 1.5 hours, ultrasonic treatment was introduced at a frequency of 20 kHz and a power of 1.5 kW for 15 minutes, and then heated to 180°C and dehydrated for 4 hours to obtain a fluorosilicone / polyurethane emulsion.

[0038] 250 parts of 1% guar gum aqueous solution, 6.25 parts of sodium hydroxide and 2 parts of iodomethane were mixed and stirred for 2.5 hours under a nitrogen inert atmosphere, and then acetic acid was added to adjust the pH value of the solution to 7.0. After adding 250 parts of acetone to precipitate the synthetic product, the precipitate was washed 3 times with 200 parts of 50% acetone solution to remove any unreacted chemicals and salts formed during the neutralization process, and freeze-dried to obtain methylated guar gum powder; 10 parts of methylated guar gum powder were dissolved in 25 parts of 10% hydrophobic nanoclay water suspension (nanoclay model: Cloisite 20A), 10 parts of ethanol dispersion of nano-alumina and nano-titanium dioxide were added, and after ultrasonic treatment for 1.2 hours, mechanical stirring was carried out at 20 rpm at room temperature for 30 minutes to obtain a methylated guar gum-based composite material.

[0039] Inject 4 parts of fluorosilicone / polyurethane emulsion into a 10ml syringe and install it on the syringe pump, connect the catheter through the female Luer head, and then connect the spinning nozzle through the male Luer head. At the same time, clamp the spinning nozzle on the high-voltage power supply and adjust the nozzle to a suitable position. Then, wrap the spinning substrate aluminum foil on the roller receiving the spinning device. Set the spinning parameters as follows: solution push speed 2.0ml / h, spinning nozzle moving speed 2.3mm / s, substrate spacing 14cm, roller-type aluminum foil receiving substrate, rotation speed 235r / min, spinning DC voltage 12.1kV, stable spinning for 2h; place the electrospun film under natural conditions to dry for 16h, so that the solvent in the film can be completely volatilized, and obtain a fluorosilicone / polyurethane film.

[0040] 0.2 parts of polytetrahydrofuran diamine were added to 3 parts of methylated guar gum-based composite materials, and then gently stirred at room temperature for 17 minutes, and brushed with a brush at 180 g / m 2 After being coated on the fluorosilicone / polyurethane film at a coating rate of , it was allowed to stand at 25°C for 40 hours to cure, thereby obtaining an anti-corrosion polyurethane composite protective film.

[0041] Example 4 35 parts of fluorosilicone resin, 50 parts of polyurethane suspension, 40 parts of propylene glycol methyl acetate and 5 parts of triphenyl phosphite were mixed uniformly at a speed of 25 rpm with mechanical stirring for 1.5 hours, ultrasonic treatment was introduced at a frequency of 20 kHz and a power of 1.5 kW for 18 minutes, and then heated to 170°C and dehydrated for 4.5 hours to obtain a fluorosilicone / polyurethane emulsion.

[0042] 1 part of graphene oxide sheet was added to 10 parts of anhydrous ethanol solution, and ultrasonic treatment was performed for 20 minutes to obtain a graphene oxide sheet suspension; 8 parts of graphene oxide sheet suspension and 5 parts of γ-glycidyloxypropyltrimethoxysilane (KH-560) were stirred for 15 minutes to mix, and 66.7% acetic acid solution was slowly added to the solution, and the pH value was adjusted to about 5. After reacting at 75°C for 24 hours, it was dried at 24°C for 40 hours to obtain hyperbranched graphene oxide; 250 parts of 1% guar gum aqueous solution and 6 .25 parts of sodium hydroxide and 2 parts of iodomethane were mixed and stirred for 3 hours under a nitrogen inert atmosphere, and then acetic acid was added to adjust the pH value of the solution to 7.0. After adding 250 parts of acetone to precipitate the synthetic product, the precipitate was washed 3 times with 200 parts of 50% acetone solution to remove any unreacted chemicals and salts formed during the neutralization process, and freeze-dried to obtain methylated guar gum powder; 13 parts of methylated guar gum powder were dissolved in 40 parts of 8% hydrophobic nanoclay aqueous suspension (nanoclay model: Cloisite 20A), 8 parts of ethanol dispersion of nano-alumina and nano-titanium dioxide and 0.2 parts of hyperbranched graphene oxide were added, and after ultrasonic treatment for 1.5 hours, mechanical stirring was carried out at 20 rpm at room temperature for 55 minutes to obtain a methylated guar gum-based composite material.

[0043] 3.5 parts of fluorosilicone / polyurethane emulsion were injected into a 10ml syringe and installed on the syringe pump. The catheter was connected through the female Luer head, and then the spinning nozzle was connected through the male Luer head. At the same time, the spinning nozzle was clamped on the high-voltage power supply and adjusted to a suitable position. Subsequently, the spinning substrate aluminum foil was wrapped on the roller receiving the spinning device. The spinning parameters were set as follows: solution push speed 2.0ml / h, spinning nozzle moving speed 2.3mm / s, substrate spacing 14cm, roller-type aluminum foil receiving substrate, rotation speed 235r / min, spinning DC voltage 12.1kV, stable spinning for 2h; the film after electrospinning was placed under natural conditions for drying for 20h to allow the solvent in the film to completely evaporate, and a fluorosilicone / polyurethane film was obtained.

[0044] 0.6 parts of polytetrahydrofuran diamine were added to 4 parts of methylated guar gum-based composite materials, and then gently stirred at room temperature for 18 minutes, and then brushed with a brush at 180 g / m 2After being coated on the fluorosilicone / polyurethane film at a coating rate of , it was allowed to stand at 25°C for 36 hours to cure, thereby obtaining an anti-corrosion polyurethane composite protective film.

[0045] Example 5 30 parts of fluorosilicone resin, 60 parts of polyurethane suspension, 40 parts of propylene glycol methyl acetate and 5 parts of triphenyl phosphite were mixed uniformly with mechanical stirring at a speed of 25 rpm for 2 hours, ultrasonic treatment was introduced at a frequency of 20 kHz and a power of 1.5 kW for 16 minutes, and then heated to 170°C and dehydrated for 4.5 hours to obtain a fluorosilicone / polyurethane emulsion.

[0046] 250 parts of 1% guar gum aqueous solution, 6.25 parts of sodium hydroxide and 2 parts of iodomethane were mixed and stirred for 3 hours under a nitrogen inert atmosphere, and then acetic acid was added to adjust the pH value of the solution to 7.0. After adding 250 parts of acetone to precipitate the synthetic product, the precipitate was washed 3 times with 200 parts of 50% acetone solution to remove any unreacted chemicals and salts formed during the neutralization process, and freeze-dried to obtain methylated guar gum powder; 16 parts of methylated guar gum powder were dissolved in 40 parts of 7% hydrophobic nanoclay aqueous suspension (nanoclay model: Cloisite 20A), 12 parts of ethanol dispersion of nano-alumina and nano-titanium dioxide were added, and after ultrasonic treatment for 1.3 hours, mechanical stirring was carried out at 20 rpm at room temperature for 45 minutes to obtain a methylated guar gum-based composite material.

[0047] 4.5 parts of fluorosilicone / polyurethane emulsion were injected into a 10ml syringe and installed on the syringe pump. The catheter was connected through the female Luer head, and then the spinning nozzle was connected through the male Luer head. At the same time, the spinning nozzle was clamped on the high-voltage power supply and adjusted to a suitable position. Subsequently, the spinning substrate aluminum foil was wrapped on the roller receiving the spinning device. The spinning parameters were set as follows: solution push speed 2.0ml / h, spinning nozzle moving speed 2.3mm / s, substrate spacing 14cm, roller-type aluminum foil receiving substrate, rotation speed 235r / min, spinning DC voltage 12.1kV, stable spinning for 2h; the film after electrospinning was placed under natural conditions for drying for 24h to allow the solvent in the film to completely evaporate, and a fluorosilicone / polyurethane film was obtained.

[0048] 0.9 parts of polytetrahydrofuran diamine were added to 7 parts of methylated guar gum-based composite materials, and then gently stirred at room temperature for 16 minutes, and then brushed with a brush at 180 g / m 2 After being coated on the fluorosilicone / polyurethane film at a coating rate of , it was allowed to stand at 30°C for 45 hours to cure, thereby obtaining an anti-corrosion polyurethane composite protective film.

[0049] Example 6 20 parts of fluorosilicone resin, 40 parts of polyurethane suspension, 40 parts of propylene glycol methyl acetate and 5 parts of triphenyl phosphite were mixed uniformly with mechanical stirring at a speed of 25 rpm for 1 hour, ultrasonic treatment was introduced at a frequency of 20 kHz and a power of 1.5 kW for 10 minutes, and then heated to 160°C and dehydrated for 3 hours to obtain a fluorosilicone / polyurethane emulsion.

[0050] 1 part of graphene oxide sheet was added to 10 parts of anhydrous ethanol solution, and ultrasonic treatment was performed for 20 minutes to obtain a graphene oxide sheet suspension; 8 parts of graphene oxide sheet suspension and 5 parts of γ-glycidyloxypropyltrimethoxysilane (KH-560) were stirred for 15 minutes to mix, and 66.7% acetic acid solution was slowly added to the solution, and the pH value was adjusted to about 5. After reacting at 75°C for 24 hours, it was dried at 24°C for 40 hours to obtain hyperbranched graphene oxide; 250 parts of 1% guar gum aqueous solution and 6 .25 parts of sodium hydroxide and 2 parts of iodomethane were mixed and stirred for 3 hours under a nitrogen inert atmosphere, and then acetic acid was added to adjust the pH value of the solution to 7.0. After adding 250 parts of acetone to precipitate the synthetic product, the precipitate was washed 3 times with 200 parts of 50% acetone solution to remove any unreacted chemicals and salts formed during the neutralization process, and freeze-dried to obtain methylated guar gum powder; 12 parts of methylated guar gum powder were dissolved in 65 parts of 6% hydrophobic nanoclay aqueous suspension (nanoclay model: Cloisite 20A), 10 parts of ethanol dispersion of nano-alumina and nano-titanium dioxide and 0.5 parts of hyperbranched graphene oxide were added, and after ultrasonic treatment for 1.2 hours, mechanical stirring was carried out at 20 rpm at room temperature for 50 minutes to obtain a methylated guar gum-based composite material.

[0051] Inject 3 parts of fluorosilicone / polyurethane emulsion into a 10ml syringe and install it on the syringe pump, connect the catheter through the female Luer head, and then connect the spinning nozzle through the male Luer head. At the same time, clamp the spinning nozzle on the high-voltage power supply and adjust the nozzle to a suitable position. Then, wrap the spinning substrate aluminum foil on the roller receiving the spinning device. Set the spinning parameters as follows: solution push speed 2.0ml / h, spinning nozzle moving speed 2.3mm / s, substrate spacing 14cm, roller-type aluminum foil receiving substrate, rotation speed 235r / min, spinning DC voltage 12.1kV, stable spinning for 2h; place the electrospun film under natural conditions to dry for 12h, so that the solvent in the film can be completely volatilized, and obtain a fluorosilicone / polyurethane film.

[0052] 0.8 parts of polytetrahydrofuran diamine was added to 6 parts of methylated guar gum-based composite materials, and then gently stirred at room temperature for 15 minutes, and then brushed with a brush at 180 g / m 2 After being coated on the fluorosilicone / polyurethane film at a coating rate of , it was allowed to stand at 20°C for 32 hours to cure, thereby obtaining an anti-corrosion polyurethane composite protective film.

[0053] The present invention also carries out comparative examples and related tests.

[0054] Comparative Example 1 The only difference compared with Example 1 is that the methylated guar gum-based composite material is not prepared as an outer layer to be coated on the fluorosilicone / polyurethane film, but is directly prepared from the fluorosilicone / polyurethane emulsion by electrospinning. The other components and preparation steps are exactly the same to obtain an anti-corrosion polyurethane composite protective film.

[0055] Comparative Example 2 The only difference compared with Example 2 is that the outer layer film raw material of the anti-corrosion polyurethane composite protective film is directly used as a mixture of methylated guar gum powder and hydrophobic nano-clay water suspension, and no ethanol dispersion of nano-alumina and nano-titanium dioxide is added as filler. The other components and preparation steps are completely the same to obtain an anti-corrosion polyurethane composite protective film.

[0056] Comparative Example 3 The only difference compared with Example 1 is that no fluorosilicone / polyurethane emulsion is prepared, and the inner layer membrane is prepared directly by electrospinning using polyurethane emulsion. The other components and preparation steps are exactly the same, and finally an anti-corrosion polyurethane composite protective film is obtained.

[0057] Comparative Example 4 The only difference compared with Example 2 is that methylated guar gum powder is not prepared, and guar gum powder is directly used. The other components and preparation steps are completely the same, and finally an anti-corrosion polyurethane composite protective film is prepared.

[0058] Comparative Example 5 The only difference compared with Example 2 is that the hydrophobic nanoclay aqueous suspension is not added, and the other components and preparation steps are completely the same, and finally an anti-corrosion polyurethane composite protective film is obtained.

[0059] Comparative Example 6 The only difference compared with Example 2 is that the fluorosilicone / polyurethane film is not prepared by electrospinning, but is directly prepared by high-temperature hot pressing. The other components and preparation steps are completely the same to obtain an anti-corrosion polyurethane composite protective film.

[0060] The basic performance tests were conducted on the anti-corrosion polyurethane composite protective films for batteries prepared in Examples 1 to 6 and Comparative Examples 1 to 6. The total thickness, elongation at break, tensile strength, and density were tested in accordance with the national standard HG / T5070-2016 for thermoplastic polyurethane (TPU) films, with the requirements of elongation at break (%) ≥ 350 and tensile strength MPa ≥ 30.0; the yellowness index was tested in accordance with the national standard GB / T36289.1-2018 for insulating films for crystalline silicon solar cell modules Part 1: polyester films, with the requirement of yellowness index (YI) ≤ 3.0. The basic performance test results are shown in Table 1.

[0061] Table 1

[0062] As shown in Table 1, Examples 1 to 6 all meet the national standards HG / T5070-2016 Thermoplastic Polyurethane (TPU) Film and GB / T36289.1-2018 Insulating Film for Crystalline Silicon Solar Cell Module Part 1: Polyester Film. Combined with the data in Table 1, it can be seen that the yellowness coefficient of the anti-corrosion polyurethane composite protective film prepared in Comparative Example 1 due to the lack of preparation of the methylated guar gum-based composite material as the outer film and Comparative Example 2 due to the lack of addition of the ethanol dispersion of nano-alumina and nano-titanium dioxide as the filler of the outer film has obvious defects; Examples 1, 4, and 6 add hyperbranched graphene oxide to the methylated guar gum-based composite material, so that the basic performance of the anti-corrosion polyurethane composite protective film prepared is also improved.

[0063] The anti-corrosion polyurethane composite protective films prepared in Examples 1 to 6 and Comparative Examples 1 to 6 were subjected to relevant performance tests. The shrinkage rate, volume resistivity, and water vapor permeability were tested in accordance with the national standard GB / T36289.1-2018 Insulating film for crystalline silicon solar cell modules Part 1: Polyester film, the oxygen permeability and ultraviolet light transmittance were tested in accordance with the national standard GB / T36289.2-2018 Insulating film for crystalline silicon solar cell modules Part 2: Fluoroplastic film, the water vapor permeability was tested with reference to the standard of HG / T5877-2021 Thermoplastic polyurethane (TPU) granules for waterproof and breathable films, and the oxygen permeability was tested in accordance with the standard method of GB / T19789-2021 Coulometer detection method for oxygen permeability test of plastic films and sheets for packaging materials, and the relevant performance test results are shown in Table 2.

[0064] Table 2

[0065] It can be seen from Table 2 that the heat resistance and insulation properties of the anti-corrosion polyurethane composite protective films prepared in Examples 1 to 6 are significantly higher than those of the anti-corrosion polyurethane composite protective films prepared in Comparative Examples 1 to 6; the transmittances of oxygen, water vapor and ultraviolet light are significantly lower than those in Comparative Examples 1 to 6.

[0066] Combined with the data in Table 2, it can be seen from the comparison between Example 1 and Comparative Example 1 that the anti-corrosion polyurethane composite protective film prepared in Comparative Example 1 without using the methylated guar gum-based composite material as the outer layer film has significantly higher oxygen, water vapor and ultraviolet light transmittance than Example 1; it can be seen from the comparison between Example 2 and Comparative Example 2 that the volume resistivity of the anti-corrosion polyurethane composite protective film prepared due to the presence of nano-alumina and nano-titanium dioxide is significantly increased, and the ultraviolet light transmittance is significantly reduced; it can be seen from the comparison between Example 1 and Comparative Example 3 that the fluorosilicone / polyurethane prepared as the inner layer film has a significantly improved thermal stability. , water resistance and insulation are significantly improved, thereby improving the shrinkage, volume resistivity, oxygen, water vapor and ultraviolet light transmittance; as shown in Example 2 compared with Comparative Example 4, the use of unmethylated guar gum as the outer film raw material significantly improves the water vapor permeability; as shown in Example 2 compared with Comparative Example 5, the resistivity of the outer film without the addition of nanoclay is significantly reduced; as shown in Example 2 compared with Comparative Example 6, the volume resistivity, oxygen permeability, ultraviolet light transmittance and water vapor permeability of the anti-corrosion composite protective film prepared by electrospinning are significantly improved.

[0067] The anti-corrosion polyurethane composite protective films prepared in Examples 1 to 6 and Comparative Examples 1 to 6 were tested for acid, alkali and salt corrosion resistance. The salt spray resistance was tested according to GB / T2423.17 Environmental testing for electrical and electronic products Part 2: Test methods Test Ka: Salt spray test method, the acid resistance was tested according to the GB / T9274-1988 test method, and the alkali resistance was tested according to the GB / T9265-2009 test method. The relevant performance test results are shown in Table 3.

[0068] Table 3

[0069] It can be seen from Table 3 that the acid, alkali and salt corrosion resistance of the anti-corrosion polyurethane composite protective films prepared in Examples 1 to 6 is significantly higher than that of the anti-corrosion polyurethane composite protective films prepared in Comparative Examples 1 to 6.

[0070] The above are preferred embodiments of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A method for preparing an anti-corrosion polyurethane composite protective film for a battery, characterized in that: The following steps are involved: Step S1, mixing fluorosilicone resin, polyurethane emulsion, propylene glycol methyl acetate, and triphenyl phosphite by mechanical stirring, ultrasonic treatment, heating and dehydration, to obtain fluorosilicone / polyurethane emulsion; Step S2, mixing and stirring the methylated guar gum powder, the hydrophobic nano-clay aqueous suspension, and the ethanol dispersion of nano-alumina and nano-titanium dioxide, ultrasonically treating, and mechanically stirring to obtain a methylated guar gum-based composite material; Step S3, after preparing a fluorosilicone / polyurethane film by electrostatic spinning of a fluorosilicone / polyurethane emulsion, adding polytetrahydrofuran diamine to the methylated guar gum-based composite material, stirring, coating the fluorosilicone / polyurethane film, and standing to cure to obtain an anti-corrosion polyurethane composite protective film.

2. The method for preparing a corrosion-resistant polyurethane composite protective film for batteries according to claim 1, characterized in that: In the step S1, polyester resin is added before mechanical stirring, the speed of mechanical stirring is 25 rpm, the time is 1-2 hours, the time of ultrasonic treatment is 10-20 minutes, the temperature of heating dehydration is 160° C.-200° C., and the time is 3-5 hours.

3. The method for preparing a corrosion-resistant polyurethane composite protective film for batteries according to claim 1, characterized in that: The methylated guar gum powder in step S2 is prepared by mixing and stirring a 1% guar gum aqueous solution, sodium hydroxide and methyl iodide under a nitrogen inert atmosphere for 2.5 to 3 hours, adding acetic acid to adjust the pH value of the solution to 7.0, adding acetone, filtering and retaining the precipitate, adding a 50% acetone solution to wash three times, and then freeze-drying.

4. The method for preparing a corrosion-resistant polyurethane composite protective film for batteries according to claim 1, characterized in that: In the step S2, hyperbranched graphene oxide is also added before mixing and stirring.

5. The method for preparing a corrosion-resistant polyurethane composite protective film for batteries according to claim 4, characterized in that: The hyperbranched graphene oxide is prepared by stirring and mixing a graphene oxide sheet suspension and γ-glycidyloxypropyltrimethoxysilane, adding an acetic acid solution with a concentration of 66.7%, reacting at 75°C for 24 hours, and drying at 24°C for 40 hours; the graphene oxide sheet suspension is prepared by dispersing graphene oxide sheets in an anhydrous ethanol solution and ultrasonically treating them for 20 minutes.

6. The method for preparing a corrosion-resistant polyurethane composite protective film for batteries according to claim 1, characterized in that: In the step S2, the ultrasonic treatment time is 1-2 hours, the mechanical stirring speed is 20 rpm, and the time is 30-60 minutes; the concentration of the hydrophobic nanoclay water suspension in the step S2 is 5%-10%, and the model of the nanoclay in the hydrophobic nanoclay water suspension is Cloisite 20A.

7. The method for preparing a corrosion-resistant polyurethane composite protective film for batteries according to claim 1, characterized in that: In step S3, the electrospinning time is 2 hours, the fluorosilicone / polyurethane film after electrospinning is placed under natural conditions to dry for 12 to 24 hours, the stirring time is 15 to 20 minutes, and the static curing temperature is 20 to 30° C. and the time is 32 to 48 hours.

8. An anti-corrosion polyurethane composite protective film for batteries, characterized in that: The anti-corrosion polyurethane composite protective film for batteries is prepared by the method for preparing the anti-corrosion polyurethane composite protective film for batteries according to any one of claims 1 to 7, characterized in that the anti-corrosion polyurethane composite protective film comprises the following raw materials in parts by weight: 3 to 5 parts of fluorosilicone / polyurethane emulsion, 0.2 to 0.8 parts of polytetrahydrofuran diamine, and 3 to 7 parts of methylated guar gum-based composite material.

9. The anti-corrosion polyurethane composite protective film for batteries according to claim 8, characterized in that: The raw materials of the fluorosilicone / polyurethane emulsion include 20-50 parts of fluorosilicone resin, 40-60 parts of polyurethane emulsion, 40 parts of propylene glycol methyl acetate, and 5 parts of triphenyl phosphite in parts by weight; the raw materials of the methylated guar gum-based composite material include 10-20 parts of methylated guar gum powder, 65-80 parts of hydrophobic nanoclay water suspension, and 10-15 parts of ethanol dispersion of nano-alumina and nano-titanium dioxide in parts by weight.

10. The anti-corrosion polyurethane composite protective film for batteries according to claim 9, characterized in that: The raw materials of the methylated guar gum powder include 250 parts of guar gum aqueous solution, 6.25 parts of sodium hydroxide and 2 parts of methyl iodide calculated by weight.

Citation Information

Patent Citations

  • Corrosion-resistant waterproof moisture-permeable composite fabric and preparation method thereof

    CN114714709A